Analisis Kebutuhan Reagen Kimia Klinik Dan Pengelolaan Safety Stock Menggunakan Time Series Di RSUD Siti Fatimah - Ulfah, Nisrina; Andalia, Winny; MZ, Hermanto (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2025)
Clinical chemistry reagents are important components in supporting the smooth running of medical laboratory examinations. Timely availability of these reagents significantly affects the speed and accuracy of diagnoses. Meanwhile, at Siti Fatimah Hospital, reagent management faces challenges due to fluctuations in demand and delays in procurement, potentially hindering services and leading to patient referrals to external facilities. For this reason, a more accurate planning strategy is needed. One of them is through the application of the Production and Operations Management (POM) principle, which can increase efficiency in managing Safety stock based on historical data. This study aims to develop a forecasting model for the need for Creatinine, blood urea, and alkaline phosphatase reagents. Then, design an optimal Safety stock plan to anticipate demand uncertainty.This study uses a quantitative descriptive method. Data were collected through observation, interviews, and documentation. Data were processed using QM for Windows software to obtain time series forecasting results and Safety stock calculations. The results of the analysis showed that the linear trend method was the best forecasting method for the need for Creatinine and blood urea reagents. For alkaline phosphatase, the best method is Exponential Smoothing With Trend. Then, in the calculation of Safety stock, the assumption of a service level of 95% produces reserves of 99.56 mL for Creatinine, 87.85 mL for blood urea, and 3.80 mL for alkaline phosphatase. This method proves effective in ensuring optimal reagent availability and minimizing stockout risks.